EXPLORING THE CONNECTIONS BETWEEN NARRATIVE AND SUGGESTIVE, OR ABOUT PROGRAMMISM IN VIOLIN CONCERTOS AND ORCHESTRAS FROM THE 20TH CENTURY - MELNIC, VICTORIA; CIOBANU, GHENADIE (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică)
Today, violin and orchestra concerts undergo a profound transformation, evolving into complex musical narratives that explore deep themes and emotions. Programmatic titles and other indications convey composers’ intention to imbue their works with aesthetic or philosophical landmarks, thus strengthening the connection between music and programmatic content. This evolution brings a new dimension to the concert genre, where programmatic elements become essential in expressing composers’ visions in communicating with the audience and guiding listeners towards specific styles, aesthetics, or moods, contributing to the individualization and conceptualization of the work. The interaction between music and programmatic content adds a new depth to the concert genre, highlighting composers’ ability to convey complex ideas through music. Thus, violin and orchestra concerts become captivating musical narratives, reflecting the diversity and innovation in the art of musical composition.